Preoperative Status of Gut Microbiota Predicts Postoperative Delirium in Patients With Gastric Cancer - Liu, Hu; Cheng, Gao; Xu, Yuan-ling; Fang, Qi; Ye, Lei; Wang, Chun-hui; Liu, Xue-sheng (Frontiers in Psychiatry, 2022)
Introduction: Post-operative delirium (POD) is a serious complication which occurs after surgery, especially in the elderly undergoing abdominal surgery. Increasing evidence has revealed an association between the gut microbiota and psychological disorders involving the “brain-gut” axis. However, the association between the pathogenesis of POD after abdominal surgery in aging and composition of the gut microbiota remains unclear. Methods: Forty patients (≥65 years old) who underwent abdominal surgery were included in the study. Twenty patients had POD, whereas 20 patients did not. POD was diagnosed and assessed using the confusion assessment method (CAM) during the postoperative period. Total RNA fractions were extracted from all fecal samples of patients. 16S and 23S rRNA sequencing was performed to determine the composition of the gut microbiota. The quality of the samples was determined by calculating the α- and β-diversities. Results: The α- and β-diversities indicated that the samples were eligible for detection and comparison. We observed multiple differentially abundant bacteria in patients with and without POD. Generally, Proteobacteria, Enterbacteriaceae, Escherichia Shigella, Klebsiella, Ruminococcus, Roseburia, Blautia, Holdemanella, Anaerostipes, Burkholderiaceae, Peptococcus, Lactobacillus, and Dorea were abundant in the POD cohort, whereas Streptococcus equinus and Blautia hominis were abundant in the control cohort. The results of receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) of Escherichia Shigella was 0.75. Phenotype prediction showed that the gut microbiota may influence POD by altering the tolerance to oxidative stress. Conclusion: There were significant associations between the pathogenesis of POD and composition of the gut microbiota. Escherichia Shigella are promising diagnostic bacterial species for predicting POD onset after abdominal surgery in elderly people. Keywords: Surgery; Aging; Gut microbiota; Post-operative delirium; Prediction; Shigella Trial registration: ChiCTR200030131 (Chinese Clinical Trial Registry, http://www.chictr.org.cn/index.aspx), Date of registration: 24/02/ 2020